Suplementação com mix de ômegas 3, 6 e 9 sobre marcadores oxidativos e comportamentais de neuroplasticidade em camundongos - Casadevall, Meyssa Quezado de Figueiredo Cavalcante (2019)
Polyunsaturated fatty acids are essential and fat-soluble lipophilic vitamins are embedded in the fats of natural foods, playing an essential role in the body's metabolism and physiology. Consumption of polyunsaturated fatty acids may promote the modification of these factors by supplementing these acids, although the use of ω-6 and ω-9 is still poorly explored. In addition, supplementation may favor neuronal processes and influence the immune and inflammatory response, thus aiding in disease prevention. However, this study evaluated the action of omega 3, 6, and 9 3% supplementation on oxidative, inflammatory, biochemical, and behavioral markers in healthy C57bl6 mice. Fifty-four mice were divided into three groups: control fed the standard diet and two test groups fed lactose-free skim milk or lactosefree skim milk supplemented with 3% fat enriched with omega 3, 6 and 9 emulsion. first divided into three groups (n = 18 / group) and then subdivided into the group itself with n = 9 / group fed for 45 or 60 days. After the days of diet, the animals were submitted to behavioral tests for memory and cognition evaluation (Y maze test and Morris water maze test) and locomotor activity evaluation (open field test). After the last behavioral test, the animals were euthanized by decapitation and had their hippocampus dissected and stored at -80º C for further analysis of oxidative stress (TBARS and GSH), inflammatory response (MPO) and processed according to the protocol of the technique. Golgi Cox. Retroorbital venous plexus blood was collected for biochemical tests (Blood Glucose, AST, ALT, Urea and Creatinine) and oxidative stress (TBARS and GSH). We observed that the supply of skim milk supplemented with omega 3, 6 and 9 mix increased grooming behavior and improved memory.Mix supplementation demonstrated an antioxidant effect on hippocampus and plasma. On the other hand, MPO levels were higher in animals receiving this type of diet. Regarding peripheral toxicity, supplementation caused a reduction in AST and blood glucose concentration and did not cause differences in ALT, urea and creatinine levels. A possible protective action on liver and renal functions was observed, and no influence on markers of renal function. It also demonstrates neuronal protective effect by increasing neuronal density, dendrite length and number of synapses after 45 and 60 days of supplementation. The results show the beneficial effects of omega-mix supplementation on lipoprotein profile, inflammatory and neurological disorders in treated animals, which can prevent various types of diseases, especially chronic degenerative diseases such as Alzheimer's, multiple sclerosis, diabetes and even cancer. To complement preclinical findings, clinical studies, and the evaluation of cytotoxicity of these compounds, they may suggest new treatment strategies and confirm the effects of omega mix supplementation on quality of life and disease prevention.